Impact of baicalin and components of Scutellaria baicalensis on renal fibrosis of diabetic kidney disease - Li, Jiarui; Zhuang, Yuan; Fan, Guoyong; Wang, Simeng; Yan, Enhui; Guo, Jianpeng; Zhang, Chi; Jiang, Shicui (Frontiers in Pharmacology, 2024)
Background Fibrosis is key in the development and progression of diabetic kidney disease (DKD). Baicalin (BA), wogonin (WGN), and wogonoside (WGS) have renoprotective effects. The mechanism of alleviation of DKD progression, by improving renal fibrosis, is unclear. This study aimed to investigate the mechanisms and effects of a Scutellaria baicalensis Georgi. (Lamiaceae) mixture (MIX, WGN:BA:WGS = 4:2:1) on DKD in a spontaneous DKD model. Methods Male db/m mice were controls, and db/db mice were diabetes models. Both groups received daily oral gavage of normal saline. Treatment groups received daily oral gavage of BA or MIX (20 mg/kg) for 10 weeks. Biochemical indicators and kidney lesions were assessed. Fibrosis-related proteins were detected by immunoblotting, immunohistochemistry, and real-time fluorescence quantitative PCR. Results MIX significantly reduced body weight (40.97 ± 1.43 vs. 42.26 ± 1.60), improved insulin sensitivity (63.70 ± 8.98 vs. 109.48 ± 0.69), lowered the renal hypertrophy index (19.81 ± 2.86 vs. 28.94 ± 0.256), and decreased blood urea nitrogen levels (7.57 ± 0.79 vs. 9.57 ± 0.38) and the urine protein/creatinine ratio (0.50 ± 0.06 vs. 0.80 ± 0.18). MIX also enhanced lipid profiles and renal function by improving renal tubular dilation, restoring renal structures, and reducing glomerulosclerosis, basal membrane thickening, and glycogen deposition. These effects were achieved by reducing the protein and gene expression of collagen II (Col-II), connective tissue growth factor, and collagen I (Col-I). Conclusion MIX inhibits the transforming growth factor-β/Smads signaling pathway, thus alleviating renal fibrosis, and can be used to develop a treatment for DKD.